2011
DOI: 10.2176/nmc.51.8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Motor Cortex Stimulation for Intractable Central Neuropathic Pain: Comparison of Stimulation Parameters Between Post-stroke Pain and Other Central Pain

Abstract: Motor cortex stimulation (MCS) has now become the preferred option for neurosurgical management of intractable central neuropathic pain such as post-stroke pain and trigeminal neuropathic pain. However, the efficacy of MCS for other central neuropathic pain such as pain resulting from spinal cord or brainstem lesions is unclear. We retrospectively reviewed 11 consecutive patients with intractable central neuropathic pain who underwent MCS in our institution. Eight patients had poststroke pain caused by thalami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
0
15
0
1
Order By: Relevance
“…This study suggests that EBS, tDCS, and TMS neurostimulation current density distributions are altered in the presence of strokes in a manner that may explain discrepancies in CPSP treatment outcomes across the different stimulation techniques (André-Obadia et al, 2008, 2011, 2014; Hosomi et al, 2008, 2013; Lefaucheur et al, 2008, 2011a,b; Velasco et al, 2008; Tanei et al, 2011; Sachs et al, 2014). Currents flow down the path of least resistance, in the highly conductive CSF at an infarction location, and impact the current density distributions in magnitude, location, and orientation for EBS ( Figure 1 ), TMS ( Figure 2A ), and tDCS ( Figure 2B ) (Wagner et al, 2006, 2007a,b, 2009).…”
Section: Discussionmentioning
confidence: 83%
“…This study suggests that EBS, tDCS, and TMS neurostimulation current density distributions are altered in the presence of strokes in a manner that may explain discrepancies in CPSP treatment outcomes across the different stimulation techniques (André-Obadia et al, 2008, 2011, 2014; Hosomi et al, 2008, 2013; Lefaucheur et al, 2008, 2011a,b; Velasco et al, 2008; Tanei et al, 2011; Sachs et al, 2014). Currents flow down the path of least resistance, in the highly conductive CSF at an infarction location, and impact the current density distributions in magnitude, location, and orientation for EBS ( Figure 1 ), TMS ( Figure 2A ), and tDCS ( Figure 2B ) (Wagner et al, 2006, 2007a,b, 2009).…”
Section: Discussionmentioning
confidence: 83%
“…This situation occurs in neuropathic trigeminal pain; in thalamic syndrome, patients generally report no sensations. The experience of other researchers indicates significant improvements in the effectiveness of MCS after changing the stimulation parameters [20,21]. In order to overcome habituation, the authors change the mode from cycling to continuous stimulation or vice versa, and in cycling mode the off period is prolonged or shortened.…”
Section: Discussionmentioning
confidence: 99%
“…[52557637880104] These scales are applied in the preoperative, during the trial, as well as in the postoperative period and follow-ups. In some studies the pain outcome was also reported according to a pain relief scale, similar to this one, but there is some variation between the reports in the ranges of percentages: [77111]…”
Section: Discussionmentioning
confidence: 99%
“…[118119120] In the worldwide literature, there is a growing interest on stimulation of the motor cortex for treatment of FCNP [Figure 1]. [96] Initially tried for thalamic pain, it has been tried for many treatment-resistant pain syndromes [54] such as phantom limb pain, [95101106] postherpetic neuralgia, brachial plexus avulsion, [57] poststroke pain, [324648505176106111] Wallenberg syndrome,[3349] complex regional pain syndrome, [2770108] pain secondary to multiple sclerosis, [112] spinal cord injury pain, [88113] and posttraumatic brain injury pain. [107] Recently, MCS has also been tried in other nonpainful conditions.…”
Section: Introductionmentioning
confidence: 99%